Cutting an NKG2D Ligand Short: Cellular Processing of the Peculiar Human NKG2D Ligand ULBP4 - Zöller, Tobias; Wittenbrink, Mareike; Hoffmeister, Meike; Steinle, Alexander (Frontiers in Immunology, 2018)
Stress-induced cell surface expression of MHC class I-related glycoproteins of the MIC and ULBP families allows for immune recognition of dangerous "self cells" by human cytotoxic lymphocytes via the NKG2D receptor. With two MIC molecules (MICA, MICB) and six ULBP molecules (ULBP1-6), there are a total of eight human NKG2DL ligands (NKG2DL). Since the discovery of the NKG2D-NKG2DL system, the cause for both redundancy and diversity of NKG2DL has been a major matter of debate. NKG2DL diversity has been attributed, amongst others, to the selective pressure by viral immunoevasins, to diverse regulation of expression, to differential tissue expression as well as to variations in receptor interactions. Here we critically review the current state of knowledge on the poorly studied human NKG2DL ULBP4. Summarizing available facts and previous studies, we picture ULBP4 as a peculiar ULBP family member distinct from other ULBP family members by various aspects. In addition, we provide novel experimental evidence suggesting that cellular processing gives rise to mature ULBP4 glycoproteins different to previous reports. Finally, we report on the proteolytic release of soluble ULBP4 and discuss these results in the light of known mechanisms for generation of soluble NKG2DL.